Virulence of entomopathogenic nematodes to control Aeneolamia varia (Hemiptera: Cercopidae) in sugarcane - MORENO-SALGUERO, CARLOS ANDRÉS; BUSTILLO-PARDEY, ALEX ENRIQUE; LÓPEZ-NÚÑEZ, JUAN CARLOS; CASTRO-VALDERRAMA, ULISES; RAMÍREZ-SÁNCHEZ, GERSON DARÍO (Revista Colombiana de Entomología, 2012)
The spittlebug, Aeneolamia varia (Hemiptera: Cercopidae) is a limiting pest of sugarcane crops in Venezuela. In Colombia, this species has been recorded for over 40 years in Llanos Orientales, attacking pastures. Only in 2007 this insect was detected in sugarcane crops in the Cauca Valley, where we are looking at biological control agents, particularly entomopathogenic nematodes. In this study, we evaluated the virulence of three entomopathogenic nematode species selected in previous laboratory and greenhouse studies, Steinernema sp.1, Heterorhabditis bacteriophora and Hete rorhabditis sp. (Gua 31), and two commercially aviable species, Steinernema sp. and Heterorhabditis sp., on IV instar nymphs of A. varia. The most virulent isolates were Heterorhabditis sp. (Gua 31) causing 42.3% of mortality at a dosage of 5 x 1010 JI/ha, and Heterorhabditis bacteriophora in dosage of 1.5 x 1011 JI/ha causing 76% of mortality on nymphs. This information is intended to give the farmer an effective alternative for the integrated management of A. varia.